The impact of working conditions on mental health: novel evidence from the UK - Michele Belloni; Ludovico Carrino; Elena Meschi (Global Labor Organization (GLO), 2022)
This paper investigates the causal impact of working conditions on mental health in the UK, combining new comprehensive longitudinal data on working conditions from the European Working Condition Survey with microdata from the UK Household Longitudinal Survey (Understanding Society). Our empirical strategy accounts for the endogenous sorting of individuals into occupations by including individual fixed effects. It addresses the potential endogeneity of occupational change over time by focusing only on individuals who remain in the same occupation (same ISCO), exploiting the variation in working conditions within each occupation over time. This variation, determined primarily by general macroeconomic conditions, is likely to be exogenous from the individual point of view. Our results indicate that improvements in working conditions have a beneficial, statistically significant, and clinically meaningful impact on depressive symptoms for women. A one standard deviation increase in the skills and discretion index reduces depression score by 2.84 points, which corresponds to approximately 20% of the GHQ score standard deviation, while a one standard deviation increase in working time quality reduces depression score by 0.97 points. The results differ by age: improvements in skills and discretion benefit younger workers (through increases in decision latitude and training) and older workers (through higher cognitive roles), as do improvements in working time quality; changes in work intensity and physical environment affect only younger and older workers, respectively. Each aspect of job quality impacts different dimensions of mental health. Specifically, skills and discretion primarily affect the loss of confidence and anxiety; working time quality impacts anxiety and social dysfunction; work intensity affects the feeling of social dysfunction among young female workers. Finally, we show that improvements in levels of job control (higher skills and discretion) and job demand (lower intensity) lead to greater health benefits, especially for occupations that are inherently characterised by higher job strain.
Keywords: I1; J24; J28; J81; 330; mental health; working conditions; job demand; job control